The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/biomedicines9121763
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Spectroscopic and In Silico Approach to Evaluate the Interaction of Human Frataxin with Mitochondrial Superoxide Dismutase

Abstract: Frataxin (FXN) is a highly conserved mitochondrial protein whose deficiency causes Friedreich’s ataxia, a neurodegenerative disease. The precise physiological function of FXN is still unclear; however, there is experimental evidence that the protein is involved in biosynthetic iron–sulfur cluster machinery, redox imbalance, and iron homeostasis. FXN is synthesized in the cytosol and imported into the mitochondria, where it is proteolytically cleaved to the mature form. Its involvement in the redox imbalance su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Among them, 66 genes were upregulated in miR-150-KO antigen-specific CD4 + T cells and 4 genes were known to participate in reducing superoxide byproducts that are pro-apoptotic. Both superoxidedismutase-2 (SOD2) and netrin-1 (Ntn1) directly reduce superoxide products (35), while Nfe2l2 and Frataxin (Fxn) enhance and promote SOD2 function (36,37). Therefore, either directly or indirectly, miR-150 may control superoxide levels in antigen-specific CD4 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 66 genes were upregulated in miR-150-KO antigen-specific CD4 + T cells and 4 genes were known to participate in reducing superoxide byproducts that are pro-apoptotic. Both superoxidedismutase-2 (SOD2) and netrin-1 (Ntn1) directly reduce superoxide products (35), while Nfe2l2 and Frataxin (Fxn) enhance and promote SOD2 function (36,37). Therefore, either directly or indirectly, miR-150 may control superoxide levels in antigen-specific CD4 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, inherently flexible regions, such as unstructured loops, show increased flexibility in solution compared to the crystal structure, but the overall fold of the protein is not grossly distorted. The structure of isolated Nqo15 is more dynamic than that of human FXN, as determined by the comparison of the MD simulations [38]: aside from the C-terminus, the RMSF of FXN peaks at 2 Å and is, on average, lower than 1.5 Å, whereas several regions of Nqo15 have an RMSF of 2 Å or higher.…”
Section: Structural Integrity Solubility and Stability Of Standalone ...mentioning
confidence: 99%
“…The involvement of the protein in redox homeostasis is still unclear as well, but it has been demonstrated that human FXN interacts, at least in vitro, with mitochondrial superoxide dismutase (SOD2), a key enzyme involved in the defense against oxidative stress [38].…”
Section: Introductionmentioning
confidence: 99%